Analisis Kemampuan Berpikir Kritis Siswa SMP Pada Materi SPLDV - Mayang Alsya Putri; Syamsir Sainuddin; Feri Tiona Pasaribu (Media Pendidikan Matematika, 2025)
This study aims to analyze junior high school students’ critical thinking skills in solving problems related to Systems of Linear Equations in Two Variables (SPLDV). The research employed a descriptive qualitative approach and was conducted at SMP Negeri 9 Kota Jambi involving 32 ninth-grade students. Data were collected through contextual essay-type SPLDV tests designed based on six critical thinking indicators proposed by Facione, namely interpretation, analysis, evaluation, inference, explanation, and self-regulation. In-depth interviews were also conducted to support and clarify the test results. Data analysis followed an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that students’ critical thinking skills have not developed evenly across all indicators. Interpretation skills were relatively better developed, while evaluation, inference, explanation, and self-regulation remained at low levels. Most students were able to identify relevant information and construct mathematical models; however, they experienced difficulties in evaluating solution procedures and drawing logical conclusions. These results highlight the need for mathematics learning strategies that emphasize analytical reasoning, evaluation, and reflective thinking to enhance students’ critical thinking skills, particularly in learning SPLDV.